Determination of Scope of Geodetic Survey During the Operation of Buildings and Structures Subject to Effects of Man-Caused Geodinamic Processes - Hryhorovskyi, P.; Chukanova, N.; Kroshka, Yu.; Murasova, O.; Basanskyi, V. (Science and Innovation, 2023)
Introduction. Forecasting the dynamics of the progressing of building deformations with the use of the data of instrumental measurements should take into account the influence of geodynamic processes and other factors of the external environment on the operational suitability of buildings. The duration of the life cycle of buildings depends on the timely consideration of the damage threats and forecasting of changes in their technical condition under the influence of natural, man-caused, constructional, and operational factors. Problem Statement. Untimely detection and elimination of defects is the cause of damage and deformation of buildings. Purpose. The purpose of this research is to forecast the progressing defects and damage by the methods of timely assessment of the technical condition of buildings, with the use of instrumental measurement data on the influence of environmental factors on the mechanism of destruction and wear of buildings during their construction and operation. Material and Methods. The methods of analysis and generalization have been used to substantiate the relevance and to formulate the purpose and objectives of the research. The retrospective method for studying the objects over time has been used to collect statistical information and analytical materials on the main parameters of their construction and operation. To forecast the parameters of instrumental measurements at the stages of the life cycle, there have been employed the following empirical research methods: survey, monitoring, generalization of experience, expert surveys, expert evaluations, and forecasting. Risks of damage have been assessed based on the materials of engineering studies, given the possibility of hazard activation, the power and remoteness of the threat source, the technical condition of buildings, and the compaction. The initial data for choosing an effective system are: the stability of the slopes where the building is located, their steepness, the condition and geological composition of the soil base, sources of possible flooding and vibrations. Results. The authors have proposed choosing an effective system of instrumental observation of landslides during the construction and operation of buildings given the vulnerability criterion. The developed method allows choosing an effective system of landslide observations, during the construction and operation of buildings, given the mentioned criterion, i.e. the property of the building to lose serviceability as a result of its possible damage under the influence of negative factors. Conclusions. The proposed method can be used to determine the scope of instrumental observations of landslides and the periodicity of landslide control during the construction in complex geodynamic conditions.